Nanoscale Measurements of Elastic Properties and Hydrostatic Pressure in H2‐Bulged MoS2 Membranes. Issue 23 (7th October 2020) - Di Giorgio, Cinzia; Blundo, Elena; Pettinari, Giorgio; Felici, Marco; Lu, Yuerui; Cucolo, Anna Maria; Polimeni, Antonio; Bobba, Fabrizio
Abstract: The combination of extremely high stiffness and bending flexibility with tunable electrical and optical properties makes van der Waals transition metal dichalcogenides appealing both for fundamental science and applied research. By taking advantage of localized H2 ‐bulged MoS2 membranes, an innovative approach, based on atomic force microscopy nanoindentation, is demostrated and discussed here, aiming at measuring elastic and thermodynamic properties of nanoblisters made of 2D materials. The results, interpreted in the membrane limit of the Föppl–von Karman equation, lead to the quantification of the internal pressure and mole number of the trapped H2 gas, as well as of the stretching modulus and adhesion energy of the MoS2 membrane. The latter is discussed in the limit of strong (clamped and fully bonded interlayer interface) shear, as experimentally achieved in the investigated H2 ‐bulged 2D blisters. Moreover, this approach allows to quantify the stress, and consequently the strain, locally imposed to the MoS2 membrane by the bulging of the domes. Abstract : A detailed study of elastic and thermodynamic properties of nanoblisters, made on purpose in MoS2 bulk flakes by means of low‐energy proton irradiation, is provided. An experimental approach, based on atomic force microscopy (AFM) nanoindentation, is used to explore the membrane response to the bulging, the resulting membrane strain, the confinement exerted on the inner gas, and the adhesion energy.